CAR NUMBER PLATE RECOGNITION - ABDUL HAMID, SAIFUL HELMI (Universiti Teknologi PETRONAS, 2007)
The project is about car number plate recognition. In this project, program needs to be developed tbat can automatically read the number plate of tbe vehicles. Car number plate recognition is an image processing technology used to identify vehicles by their plate [7]. It has been used widely in a number of applications such as automation car parking system, security parking system, and automated payment toll. In this project, image processing work will be done by using the image processing toolbox in MATLAB. In order to identify characters form tbe vehicle's plate, image processing techniques such as extraction, enhancement, and segmentation of certain features need to be implemented for identification of the characters.